2011
DOI: 10.1016/j.yqres.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase timing of hominin occupations and the paleoenvironment in Luonan Basin, Central China

Abstract: Thousands of Paleolithic artifacts have been recovered from Paleolithic sites in the Luonan Basin, in the upper South Luohe River of central China. Their discovery suggests that the basin was an important area for hominin settlement during the Pleistocene. However, the initial timing of this occupation and the environmental conditions for this period are still largely unknown. In addition, the sediments are not well dated and most of the artifacts lie on the surface. In an attempt to resolve these issues, a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 6 publications
0
46
0
Order By: Relevance
“…N 1 refers to the braided river terrace of Weichselian Pleniglacial age, n 3 to the incised Holocene river plain (Vandenberghe et al, 1994). around the floodplain (river banks, low terraces) during warm periods. It has been suggested that in some regions, as for instance the Luonan Basin, there was differentiation in human activities under different environmental conditions (Wang, 2005;Lu et al, 2011). The termination of a settlement may have been due to increased risks of flooding (as shown, for instance, in the Upper Volga catchment; Vandenberghe et al, 2010), but in general the cause for abandonment is more difficult to appreciate as it may involve factors other than fluvio-environmental (e.g.…”
Section: Preferred Sites and Environmental Conditions For Human Settlmentioning
confidence: 99%
“…N 1 refers to the braided river terrace of Weichselian Pleniglacial age, n 3 to the incised Holocene river plain (Vandenberghe et al, 1994). around the floodplain (river banks, low terraces) during warm periods. It has been suggested that in some regions, as for instance the Luonan Basin, there was differentiation in human activities under different environmental conditions (Wang, 2005;Lu et al, 2011). The termination of a settlement may have been due to increased risks of flooding (as shown, for instance, in the Upper Volga catchment; Vandenberghe et al, 2010), but in general the cause for abandonment is more difficult to appreciate as it may involve factors other than fluvio-environmental (e.g.…”
Section: Preferred Sites and Environmental Conditions For Human Settlmentioning
confidence: 99%
“…In addition, the QMB uplift rate has generally accelerated since the mid‐Pleistocene, becoming particularly evident since the late mid‐Pleistocene (Wang et al ., ; Xue et al ., ). The Qinling Mountains in the southern part of the Loess Plateau were barriers to atmospheric circulation, as they blocked the humid/warm air masses of the EASM and the cold/dry air masses of the EAWM (Cai et al ., ; Lu et al ., ). The north area of the Qinling Mountains was affected by this obstruction, which led to an increase in the intensity of the EAWM and a decrease in the EASM.…”
Section: Discussionmentioning
confidence: 99%
“…(a) XSD stratigraphic age frame determined by comparison with the dating of the loess–paleosol layers in nearby areas, (b) Schematic diagram of the position of the XSD profile relative to the adjacent Liujiapo (LJP) (Liu, ), Baoji (BJ) (Ding et al , ), Duanjiapo (DJP) (Florindo et al , ; Wang et al , ), Luochuan (LC) (Huang et al , ; Ding et al , ; Lai, ) and Shangbaichuan (SBS) (Lu et al , ; Fang et al , ) profiles. [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Geographical and Geochronological Backgroundmentioning
confidence: 99%
“…The identical knapping technique and lithic assemblage composition and characteristics of the Palaeolithic sites in the Lantian region on the north side of the Qinling Mountains, the Luonan Basin and the Danjiang River valley in the Qinling Mountains, and the Hanzhong Basin in the south side of Qinling Mountains, indicates the similarity of the Palaeolithic assemblages in the entire Qinling Mountains area (Wang, 2005a(Wang, , 2007Wang et al, 2005Wang et al, , 2013Wang et al, , 2014. A series of Palaeolithic sites that include Acheulian assemblages in the Late Pleistocene were identified recently (Lu et al, 2007(Lu et al, , 2011Sun et al, 2012;Wang et al, 2014). Our recent discovery of stone artefacts during December 2013 surveys from the top of the Malan loess deposit in the Late Pleistocene has provided a new clue to understand the development and destination of Acheulian assemblage in East Asia, which also demonstrated the potential in revealing the physical and behavioral evolution of ancient hominins and the development of lithic technology.…”
Section: Discussionmentioning
confidence: 99%